Effect of Rebranding and Product Quality on Consumer Loyalty Through Consumer Satisfaction at Mako Cake and Bakery - Kanesha Sepdwita Nefri; Nur Efendi; Hani Damayanti Aprilia (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research aims to determine the effect of rebranding and product quality on consumer loyalty mediated by Mako Bakery consumer satisfaction. Methodology: A quantitative approach was used, population in this research were Mako Cake and Bakery consumers in Indonesia. The sampling technique was determined using purposive sampling of 385 respondents obtained from the results of distributing questionnaires. The data analysis using Partial Least Square (PLS) with SmartPLS4. Results: The results show that both rebranding and product quality significantly influence consumer satisfaction. However, consumer loyalty is only directly affected by rebranding and consumer satisfaction, while product quality indirectly influence loyalty through satisfaction. Findings: The research highlights that rebranding play a more significant role in consumer loyalty than product quality, which only indirectly affect loyalty through their impact on consumer satisfaction. Novelty: This research contributes to consumer behavior literature and the role of rebranding and product quality in customer loyalty mediated by satisfaction, particularly focusing on the bakery industry. Originality: This study is original in its focus on the large bakery industry. Conclusion: The research recommends that businesses prioritize effective rebranding and maintain product quality, to ensure a positive shopping experience to enhance consumer loyalty. Type of Paper: Research paper